Answer:
-3/5
Step-by-step explanation: I got -6/10 but you can simplify that sooo
⅔ and 8/12 form a proportion.
M=2/5 , (0,3)
use y= mx+c , find c first.
-3 = (2/5) 0 + c
c = -3
Thus the equation will be y=(2/5)x - 3.
or in some case,
(y1-y)=m(x1-x)
(-3-y)=(2/5)(0-x)
You must have been taught postulates and theorems that allow you to prove triangles congruent, such as SSS, SAS, ASA, etc. Look at the given information of a proof, and see how from the given information, using definitions, postulates, and theorems you have already learned, you can show pairs of corresponding sides and angles to be congruent that will fit into the above methods. Then use one of the methods to prove the triangles congruent.